Segmentación y análisis granulométrico de sustancia blanca y gris en IRM para el estudio del estrabismo usando transformaciones morfológicas - Mendiola Santibáñez, Jorge D.; Gallegos Duarte, Martín; Ortiz Retana, Juan José; López Campos, Carlos Enrique (Revista Mexicana de Ingenieria Biomedica, 2007)
In this paper, we present a method based on the application of morphological operators to carry out the segmentation on slices of brain magnetic resonance images (MRI). The processed slices belong to two control subjects (healthy) (CS) and one with dissociated strabismus (SS) (the three with 7 years old). Once separated the skull, we obtaining granulometric plots of white matter (WM) and grey matter (GM) located in the occipital lobe. Respect to the CS, we present a granulometric pattern for the WM as well as for the GM. Such patterns are used to be compared to the granulometric plots obtained from SS and thus being able to establish volumetric differences between the different detected structures. On the other side, in order to get the granulometric plots, equations than provide similar results to an equation of granulometric density were applied; whereas the separation of the skull is doing by a morphological transformation that avoids the generation of new structures during the processing.